Chapter On V2, gaps, and operators in comment and reporting parentheticals - Kluck, Marlies (De Gruyter, 2015)
Parenthetical comment and reporting clauses exhibit various interesting properties, which are shown to be related. Three different word order pat-terns are attested in Dutch and German: apparent V1, V2 and V-final; the internal argument of the parenthetical verb is usually missing; there is an optional so/zo element; the construction is island-sensitive. These patterns are explained by means of an operator that is A ́-moved inside the parenthetical, and which can optionally be lexicalized in the first position. The V-final pattern arises when a complementizer is present, which is the case in propositional as-parentheticals.